Clinical Outcome of Surgical Treatment of Giant Femoral Artery Pseudoaneurysms: Surgical Outcomes of Giant Femoral Artery Pseudoaneurysms - Mushtaq, Adeel; Usman, Amir; Akhtar, Ahmad Naeem; Farooq, Nazia; Jawaid, Shahzad Naveed; Ahmed, Shabbir (Pakistan Journal of Health Sciences, 2024)
Femoral artery was used as an access site for cardiovascular procedures and by IV drug abusers, Femoral Artery Pseudoaneurysm (FAP) was a common complication associated with these procedures. Objective: To evaluate clinical outcome of surgical repair of femoral artery pseudoaneurysms. Methods: The prospective study was conducted in Doctors Hospital, Lahore from October 2022 to October 2023. The study included patients with giant femoral artery pseudoaneurysms who required surgical intervention. Data from a total of 50 patients were included in whom both peripheral vascular interventions and percutaneous cardiac catheterization was performed. Patients were followed up at 1-, 3-, 6- and 12 months postoperatively. SPSS version 23.0 was used for data analysis. Results: All patients underwent open surgical treatment. Of 50 patients, 25 (50%) had SFA pseudoaneurysm, 20 (40%) had CFA pseudoaneurysm and 5 (10%) had PFA pseudoaneurysm. The mean duration of clinical manifestations was 16.30 ± 7.74 days. Surgical repair was successful in all 50 (100%) patients and distal ischemia was fully resolved. There was no case of limb loss or post-operative mortality. One patient had an infection in the groin wound and had raised Total leucocyte count (TLC), which was resolved by early drainage and antibiotic treatment. Patients were followed up at 1, 3, 6, and 12 months and there were no signs of clinical or angiographic evidence of post-operative complications and changes in distal pulse. Conclusion: Surgical repair was first-line treatment for giant FAP. It was clinically feasible and has a high success rate and low complication rate.